Institutional management: The entrepreneurial intention of the farmers of Aguascalientes - Parga-Montoya, Neftali; Vega-Martínez, Javier Eduardo; Romo-Bacco, Carlos Eduardo (Cuadernos de Administración, 2019)
The study of the institutional context is a relevant topic to measure the factors that affect the intentions of creating a firm. Based on the literature of institutional theory and the theory of planned behavior, chile producers in Mexico are analyzed. The study aims to analyze the influence of regulative, normative and cognitive burdens on the entrepreneurial intention of farmers. An empirical study was carried out with 94 producers located in the state of Aguascalientes. The hypotheses raised were contrasted from multivariate linear regressions. Important results were obtained from the influence of the normative and cognitive burdens on the intentions of entrepreneurship on the part of the producers working as a formal entity. Similarly, this work has crucial contributions to the literature related to academic training and its implications for entrepreneurial intentions, specifically being a variable that favors the penetration of institutional burdens into entrepreneurship.